Lung Epithelial TRPA1 Transduces the Extracellular ROS into Transcriptional Regulation of Lung Inflammation Induced by Cigarette Smoke: The Role of Influxed Ca2+. (4th October 2015) - Lin, An-Hsuan; Liu, Meng-Han; Ko, Hsin-Kuo; Perng, Diahn-Warng; Lee, Tzong-Shyuan; Kou, Yu Ru
Abstract : The mechanism underlying the inflammatory role of TRPA1 in lung epithelial cells (LECs) remains unclear. Here, we show that cigarette smoke extract (CSE) sequentially induced several events in LECs. The Ca 2+ influx was prevented by decreasing extracellular reactive oxygen species (ROS) with the scavenger N-acetyl-cysteine, removing extracellular Ca 2+ with the chelator EGTA, or treating with the TRPA1 antagonist HC030031. NADPH oxidase activation was abolished by its inhibitor apocynin, EGTA, or HC030031. The increased intracellular ROS was halted by apocynin, N-acetyl-cysteine, or HC030031. The activation of the MAPKs/NF- κ B signaling was suppressed by EGTA, N-acetyl-cysteine, or HC030031. IL-8 induction was inhibited by HC030031 or TRPA1 siRNA. Additionally, chronic cigarette smoke (CS) exposure in wild-type mice induced TRPA1 expression in LECs and lung tissues. In CS-exposure trpa1 −/− mice, the increased BALF level of ROS was similar to that of CS-exposure wild-type mice; yet lung inflammation was lessened. Thus, in LECs, CSE may initially increase extracellular ROS, which activate TRPA1 leading to an increase in Ca 2+ influx. The increased intracellular Ca 2+ contributes to activation of NADPH oxidase, resulting in increased intracellular ROS, which activate the MAPKs/NF- κ B signaling leading to IL-8 induction. This mechanism may possibly be at work in mice chronically exposed to CS.